Low-Cost Based Eye Tracking and Eye Gaze Estimation - I Ketut Gede Darma Putra; Agung Cahyawan; Yandi Perdana (Universitas Ahmad Dahlan, 2011)
The costs of current gaze tracking systems remain too high for general public use. The main reason for this is the cost of parts, especially high-quality cameras and lenses and cost development. This research build the low cost based for gaze tracking system. The device is built by utilizing of modified web camera in infrared spectrum. A new technique is also proposed here in order to detect the center pupil coordinate based on connected component labeling. By combination the pupils coordinate detection method with third order polynomial regression in calibration process to determine the gaze point. The experiment results show our system has an acceptable accuracy rate with error pixel 0.39o in visual degree.